HUBUNGAN KONEKSI POLITIK DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Eunike Felecia (2017)
This study was conducted to analyze the relationship Political Connections and Leverage against Tax Avoidance. The population in this study is the agricultural sector company listed in Indonesia Stock Exchange in 2013-2015. Data derived from the annual financial statements published. The sampling technique is purposive sampling method that produces for 48 samples from 16 companies during the three years of observation in 2013-2015. The research data was collected by the method of observational studies and literature study method. The analytical method used is multiple linear regression analysis. The results in this study show that the Political Connections significant negative effect on the Avoidance of Double Taxation and Leverage no significant effect on the Avoidance of Double Taxation. The results of the coefficient of determination is seen from the adjusted R-square is equal to 0.143, or 14.3%, which explains that variable taxation able to be explained by the Political Connections and leverage of 14.3%, while the remaining 85.7% is explained by other variables not used in the study.